Panama : 2020 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2020)
This 2020 Article IV Consultation with Panama discusses that focuses on Panama's near and medium-term challenges and policy priorities and was prepared before coronavirus disease 2019 became a global pandemic and resulted in unprecedented strains in global trade, commodity and financial markets. Growth is expected to recover to 4.8 percent in 2020. However, the balance of risks is tilted to the downside. A gradual fiscal consolidation can address the large fiscal imbalances while being mindful of the weak economy. Tax and customs administration reforms are needed to address the shortfall in revenues and provide room for public investment and social spending. The economic slowdown, which began in mid-2018 due to a construction strike, extended into 2019. The external current account deficit narrowed and remained adequately financed by foreign direct investment. As the economic situation in Venezuela continues to deteriorate, an increasing number of Venezuelans have migrated to Panama, creating additional social pressures.